Новые листовертки трибы Eucosmini (Lepidoptera, Tortricidae) из азиатской части СССР - Кузнецов, В.И. (Вестник зоологии, 1985)
Metacosma gen. n. is established to include Metacosma impolitana sp. n. (type-species by original designation and monotypy; type-locality: South of Primorye territory). Gypsonoma mutabilana sp. n. is described from Kurai mountain range of Altai, Epinotia notoceliana sp. n. and E. densiuncaria sp. n. from the Southern Primorye territory. The type-material is deposited in the Zoological Institute, USSR Academy of Sciences (Leningrad).